Pengujian Black Box menggunakan teknik Equivalence Partitions pada Aplikasi Sistem Pemilihan Karyawan Terbaik - Desyani, Teti; Mulyati, Sri; Kurnianto, Egi; Kamaludin, Kamaludin; Afifah, Nur; Fauziah, Siti Nur Indah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
In an application, a test is needed, to find out whether the application has errors or needs to be developed to be better. The Black Box Testing technique has been widely applied by researchers to test an application program that is appropriate or not. The software that will be tested is the best employee selection system application, and consists of a menu that will be inputted about employee data, as well as employee performance while in the company. The best employee selection system application is tested by Black Box testing. The purpose of testing this application is to see if the program performs every function we expect without looking at the source code of the software. The type of black box testing method used in this research is Equivalence Partitions. The Equivalence Partitions method is a test based on filling out each form in the best employee selection system, on each input menu will be tested and made into groups based on whether its function is valid or invalid.